Chaperone mechanisms in cellular protein folding - Hartl, F. Ulrich (Henry Stewart Talks, 2007)
The effect of protein aggregation on productive protein folding, The function of GroEL and GroES as a folding cage for proteins, Changes in energy landscape within the folding cage, Cooperation of different chaperone systems in folding pathways: Hsp70 and chaperonins, Binding of the Hsp70 homologue protein, DnaK, to newly-synthesized polypeptides, The role of chaperone mechanisms in toxicity suppression of misfolded disease causing proteins, Potential uses of the chaperone mechanisms in disease therapeutics